(untitled) (Sirte University Journal of Humanities, 2026)
This research aims to examine the implicit cultural patterns in the contemporary African novel, specifically through Chimamanda Ngozi Adichie’s "Half of a Yellow Sun." The study treats the novel as a narrative text that interrogates history, identity, and power within a postcolonial context. Drawing on the dialectic of the center and the margin, the research seeks to uncover the hidden value systems that govern the formation of novelistic discourse. Furthermore, the study focuses on analyzing the representation of cultural patterns through the main characters, particularly Richard and Ugwu, viewing them as contrasting models of the fractured colonial self and the reclamation of the local voice. The research concludes that the novel achieves a conscious deconstruction of symbolic hegemony, asserting the right of the African subject to represent its own history and suffering.